Investigation of Nursing Students' Perceptions Regarding the Educational Atmosphere of Pharmacology Course at Jahrom University of Medical Sciences - mohammad Ali montaseri; Razieh parniyan; Zohreh Badiyepeymaiejahromi; mohamad hashem abdi; Somayeh Ramezanli; Afifeh Rahmanian Koshkaki; Shohreh Javadpour; fateme kazemian (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Educational atmosphere is a manifestation of the curriculum and represents the spirit and context of schools and the curriculum. Objectives: The Dundee Ready Education Environment Measure (DREEM) is used as a diagnostic tool for evaluating the effectiveness of changes in education and identifying the difference between real and ideal environments. Accordingly, this study aimed to investigate the nursing students' perceptions regarding the educational atmosphere of the pharmacology course. Methods: This cross-sectional study was conducted on all undergraduate nursing students who had a course in pharmacology training (N=30) in 2015. To this end, the DREEM modified instrument was applied to examine students' perceptions and data were analyzed by SPSS software using mean, standard deviation, frequency, and percentage for descriptive data. Results: Overall, the mean score of the nursing students' perceptions regarding the educational atmosphere of the pharmacology course was 98.5± 18.86 out of 172. The educational atmosphere of the pharmacology course was reported as excellent (3.3%), more positive than negative (70%), and plenty of problems (26.7%) from participants' viewpoints, respectively. Conclusion: In general, the educational atmosphere of the pharmacology course was more positive than negative from the viewpoints of the majority of nursing students, indicating the importance of professors' considerations regarding the principles of the instructional design and creating an appropriate educational environment for better learning in trainings.